Rheological properties of Prosopis Chilensis Gum - AbdelHakam, Yousif Alnour (Journal of natural sciences, life and applied sciences, 2018)
In this study, twenty samples of Prosopis Chilensis gum were collected, as natural exudates, from two locations, Elsageea White Nile and Krtob ELgezera states. Two composite samples representing each location were used to prepare Rheological. The samples were Rheological the results show that the flow curves of gum solution were shown. The viscosity – shear relationships were illustrated at different concentrations (10,20,30,40 and 50% w/v ) for Prosopis Chilensis gum from different locations, when the shear rate is increased gradually (viscosity in reduced) and when the shear rate is decreased gradually (viscosity increased) the curves show a very similar behavior and comparison with Rheology of the Gum from Acacia tortilis var. tortilis.
Keywords: Rheological properties; Prosopis Chilensis gum; Gum from Acacia tortilis var; tortilis